Application of fermentation process control to increase l‐tryptophan production in Escherichia coli. (12th December 2019) - Zhao, Chunguang; Fang, Haitian; Wang, Jing; Zhang, Shasha; Zhao, Xiubao; Li, Zengliang; Lin, Chuwen; Shen, Zhiqiang; Cheng, Likun
Abstract: In this study, process engineering and process control were applied to increase the production of l ‐tryptophan using Escherichia coli D mtr / pta ‐Y. Different dissolved oxygen (DO) and pH control strategies were applied in l ‐tryptophan production. DO and pH were maintained at [20% (0–20 hr); 30% (20–40 hr)] and [7.0 (0–20 hr), 6.5 (20–40 hr)], respectively, which increased l ‐tryptophan production, glucose conversion percentage [g (l ‐tryptophan)/g (glucose)], and transcription levels of key genes for tryptophan biosynthesis and tryptophan biosynthesis flux, and decreased the accumulation of acetate and transcription levels of genes related to acetate synthesis and acetate synthesis flux. Using E. coli D mtr / pta ‐Y with optimized DO [20% (0–20 hr); 30% (20–40 hr)] and pH [7.0 (0–20 hr), 6.5 (20–40 hr)] values, the highest l ‐tryptophan production (52.57 g/L) and glucose conversion percentage (20.15%) were obtained. The l ‐tryptophan production was increased by 26.58%, the glucose conversion percentage was increased by 22.64%, and the flux of tryptophan biosynthesis was increased to 21.5% compared with different conditions for DO [50% (0–20 hr), 20% (20–40 hr)] and pH [7.0].